Changes in fatty acid composition and ratio in rat brain lipides as a predictor of the development of allergenic neuropathy under combined action of polymeric materials components - Tretyakova, E. V. (Journal of Education, Health and Sport, 2018)
Background. The nervous system failures are caused by the influence of various harmful industrial and environmental factors. Among them polymers play an important role. Polymeric materials (PM) and additive substances can be sources of significant disorders in the lipid metabolism, changes in fatty acid composition and ratio, neurotoxic effects development. But till now many aspects of such disorders mechanisms and interrelations remains unclear. Purpose. This study aimed at determining the changes in the fatty acid composition, ratio and metabolism in the brain tissues under the action of PM components combination (in particular, cadmium (Cd) and dibutyl phthalate (DBP)), to assess at the experimental model of sensitization the importance of this mechanism and show the ability to use it as an informative marker in the hygienic certification of PM. Materials and methods. The experiment was conducted on 48 white male rats of the Wistar line weighing 180-200 g. All animals divided in 4 groups: individual and combined exposure of CdCl2 and DBP with Friend’s complete adjuvant (FCA) adding and control group. The studies were performed in accordance with adaptation phases in two stages: at 33d and 72d days of chemicals administration. Complex of biomarkers were used: behavioral reactions – with the set-shifting tests "Cross maze" (CM) and "Open field" (OF); sensitization - by the reaction of specific leukocyte agglomeration (RSAL), fatty acids content – by modified Folch’s method and gas chromatography. Data processing was performed using common statistical parametric and non-parametric methods. Results. Оn the 33rd day of the experiment in animals the 2nd (DBP) and the 4th (DBP + CdCl2), the reaction of the leukocytes specific agglomeration (RLSA) index was 1.93 ± 0.12 points (p < 0.01), in 4 th - 2.06 ± 0.15 points (p < 0.001), respectively, which is a sign of the development of an allergic reaction by the delayed-type of hypersensitivity. These changes were sustainable, remaining until the end of the experiment (p < 0.01 for 72 days). The assessment of the nervous system functional activity in dynamics of the experiment revealed the earliest changes in motility in animals of the 4th group in terms of the total number of visits to the deadlocks in the CM test - a decrease of more than 2.5 times compared to the control and background indicators. Multidirectional changes were also found in the ratio of mono- / polyunsaturated fatty acids in all groups: in the 2nd and 4th the coefficient decreased by 1.43 and 1.9 times, and in the 3rd - increased by 1.3 times. The polyunsaturated FA ratio in the brain lipids of the 2nd and 4th groups also revealed a number of changes: a decrease in the total content of ω 3 unsaturated FA (USFA) and an increase in ω 6 USFA with a corresponding change in ω6 / ω3 - an increase of 3.2 and 4,2 times, respectively, in relation to the control. These disorders may play an important role in the development of cognitive disorders and neurodegenerative diseases a disregulatory nature with the combined action of the components of the PM. Conclusions. Research results are showed that an experimental model of delayed-type hypersensitivity, accompanied by changes in the spectrum and ratio of fatty acids in rat brain tissues, can be used as a complex of informative biomarkers in the process of hygienic certification of PM, studying the pathogenic mechanisms of neurotoxicity and searching for effective ways and means of protection.